Effectiveness and safety of varenicline as an aid to smoking cessation: results of an inter‐Asian observational study in real‐world clinical practice. Issue 5 (11th April 2013) - Wang, C.; Cho, B.; Xiao, D.; Wajsbrot, D.; Park, P. W.
Summary: Aims: To evaluate the effectiveness and safety of varenicline for smoking cessation among Asian adult smokers in real‐world clinical practice. Methods: A multicentre, prospective, non‐comparative, observational study conducted in China, India, Philippines and Korea. Adult smokers, willing to make a quit attempt, who reached a joint decision with the investigators to take varenicline received 1 mg twice daily (after 1‐week titration) for 12 weeks. No exclusion criteria were specified. Effectiveness evaluations included smoking abstinence status for the 7‐day period before the Week 12 visit and the last observed study visit, determined by verbal reporting using a nicotine use inventory and carbon monoxide levels if part of usual practice (end of study only). The safety profile of varenicline was also assessed. Results: Of 1377 subjects enrolled in the study, 1373 (99.7%) received varenicline and were evaluated for safety and effectiveness. Overall, 46.4% [95% confidence interval (CI): 43.73–49.07] of subjects successfully quit smoking by the end of the treatment phase at Week 12. When analysed by country, 57.1% (95% CI: 53.55–60.65) of subjects from China, 52.8% (95% CI: 45.21–60.25) of subjects from India, 51.0% (95% CI: 36.60–65.25) of subjects from Philippines and 20.3% (95% CI: 16.29–24.73) of subjects from Korea had quit smoking at Week 12. The most commonly reported treatment‐related adverse event was nausea (11.5%). Conclusions: This study demonstrates the effectiveness and acceptable safety profile of varenicline for smoking cessation in a real‐world setting among Asian populations, with results consistent with those of varenicline randomised controlled trials.